REVITALISASI KESEHATAN MENTAL ANAK USIA DINI PASCA PANDEMIC COVID 19 DENGAN PENDEKATAN PENDIDIKAN JASMANI - Hidayah, Nurul; Ismail (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The coronavirus pandemic creates many unique challenges for educators across After it was decided that in 2020 Indonesia was officially exposed to the corona virus, there was an extraordinary impact, social restrictions began to be treated or often called social distancing. The observation method, the researchers used to observe directly the method carried out by the educational institution of the Cahaya Putra Playgroup in Tegalombo Village in revitalizing the mental health of children after the COVID-19 pandemic. According to Sukmadinata observation is a technique or method of collecting data by observing activities carried out. ongoing. Results of the efforts made by educational institutions for the men's light play group in the village of Tegalombo in revitalizing children's mental health in the post-covid-19 pandemic. Using a physical education approach which is realized in the form of: 1. learning educational tours conducted at tourist attractions, 2. educational games in the form of games that involve more physical movement, 3. Learning with an emphasis on singing combined with physical movements such as dancing, gymnastics, etc.